Can a children's hospital still cut it? Comparing outcomes of pediatric, adolescent and young adult patients undergoing thoracic surgery for lung metastases. Issue 10 (29th July 2020) - Scorletti, Federico; Cooke‐Barber, Jo; Pressey, Joseph G.; Nagarajan, Rajaram; Turpin, Brian; Jenkins, Todd; Dasgupta, Roshni
Abstract: Background: Adolescents and young adults (AYAs) with cancer have unique medical challenges compared with younger children and older adults. Dedicated centers have been established to deliver cancer therapy to the AYA population; many of these programs are located in pediatric hospitals. Outcomes of AYA patients on pediatric protocols are generally superior to those on adult protocols. Little is understood about the impact of care within a pediatric environment for surgical care of young adults. Methods: A retrospective institutional review was performed of patients undergoing thoracic metastectomy between 2012 and 2017. Demographics, procedural factors, cost, and outcomes were analyzed. Patients were divided into two groups: > 18 and <18 years. Results: Ninety‐one procedures were performed: 61.5% ( n = 56) were in patients <18 years old and 38.5% ( n = 35) were > 18 years old. The median age was 6.5 years for <18 years old and 28 years for > 18 years old. Older patients had a significantly longer operative time on thoracoscopic cases; 91 versus 63 minutes. Fifty percent of the > 18 group had > 1 lesion resected compared with one lesion resected in 80.8% in <18 years old. No significant differences were found between the two groups in the duration of chest tube or length of stay. The AYA group demonstrated more "adult type" comorbidities. Conclusion: AYA patients have unique developmental and emotional challenges. Surgical intervention in this special population of patients cared for within a pediatric environment shows no significant difference in outcome compared with pediatric patients undergoing the same procedure. AYA patients with "adult type" comorbidities can safely undergo multidisciplinary care including surgery within a pediatric environment without the need to fragment care.